Mayors and Sheriffs of London - University of Toronto - Library (2022)
"The MASL database includes the mayors, sheriffs, and wardens of the City of London from 1190 to the present: their names, years of office, and companies (in the early years, craft/trade guilds) or (in the earliest years) occupations. For details on the types of information provided, including the sources for them, use the site menu bar above. Searches may be done by name, office, year, range of years, and company, and also by combinations of these. See the site menu bar on Year-of-Office Dates for information on how mayoral and shrieval terms of office are dated." [self-description]